The Influence of Social Media Marketing, Performance Expectancy, and Social Influence on Purchase Intention: Evidence from Bibit App - Agnany, Mauliddinia Iftikhar; Rofianto, Whony; Haryanti, Enny; Karambut, Fermico (Indonesia Banking School, 2025)
This study analyzes the influence of Social Media Marketing Activities (SMMA) on Brand Equity and Purchase Intention, as well as the impact of Brand Equity on Electronic Word of Mouth (E-WOM). Additionally, it examines the roles of E-WOM, Performance Expectancy (PE), and Social Influence (SI) in shaping Purchase Intention among Instagram followers of the Bibit investment application. Using a quantitative approach, data were collected from 100 respondents via convenience sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that SMMA significantly affects Brand Equity, and Brand Equity strongly influences E-WOM. However, SMMA and E-WOM were found to have no significant impact on Purchase Intention. In contrast, PE and SI proved to have a positive and significant influence on Purchase Intention. These findings suggest that for high-involvement products such as digital investment applications, functional value and social influence are more decisive in shaping purchase decisions than promotional activities or online recommendations.